Phylogenetic clustering of hepatitis C virus among people who inject drugs in Vancouver, Canada. Issue 5 (29th September 2014) - Jacka, Brendan; Applegate, Tanya; Krajden, Mel; Olmstead, Andrea; Harrigan, P. Richard; Marshall, Brandon D.L.; DeBeck, Kora; Milloy, M.‐J.; Lamoury, Francois; Pybus, Oliver G.; Lima, Viviane D.; Magiorkinis, Gkikas; et al.
<x xml:space="preserve">Abstract</x> Little is known about factors associated with hepatitis C virus (HCV) transmission among people who inject drugs (PWID). Phylogenetic clustering and associated factors were evaluated among PWID in Vancouver, Canada. Data were derived from the Vancouver Injection Drug Users Study. Participants who were HCV antibody‐positive at enrolment and those with HCV antibody seroconversion during follow‐up (1996 to 2012) were tested for HCV RNA and sequenced (Core‐E2 region). Phylogenetic trees were inferred using maximum likelihood analysis and clusters were identified using ClusterPicker (90% bootstrap threshold, 0.05 genetic distance threshold). Factors associated with clustering were assessed using logistic regression. Among 655 eligible participants, HCV genotype prevalence was: G1a: 48% (n = 313), G1b: 6% (n = 41), G2a: 3% (n = 20), G2b: 7% (n = 46), G3a: 33% (n = 213), G4a: <1% (n = 4), G6a: 1% (n = 8), G6e: <1% (n = 1), and unclassifiable: 1% (n = 9). The mean age was 36 years, 162 (25%) were female, and 164 (25%) were HIV+. Among 501 participants with HCV G1a and G3a, 31% (n = 156) were in a pair/cluster. Factors independently associated with phylogenetic clustering included: age <40 (versus age ≥40, adjusted odds ratio [AOR] = 1.64; 95% confidence interval [CI] 1.03, 2.63), human immunodeficiency virus (HIV) infection (AOR = 1.82; 95% CI 1.18, 2.81), HCV seroconversion (AOR = 3.05; 95% CI 1.40, 6.66), and recent syringe borrowing (AOR 1.59; 95% CI 1.07, 2.36). Conclusion: In this sample of PWID, one‐third demonstrated phylogenetic clustering. Factors independently associated with phylogenetic clustering included younger age, recent HCV seroconversion, prevalent HIV infection, and recent syringe borrowing. Strategies to enhance the delivery of prevention and/or treatment strategies to those with HIV and recent HCV seroconversion should be explored, given an increased likelihood of HCV transmission in these subpopulations. (Hepatology 2014;60:1571–1580)